Creative schools revolutionizing education from the ground up - Robinson, Ken 1950-2020 (Lane, 2015)
In Creative Schools Ken Robinson sets out his practical vision for how education can be transformed to enable all young people to flourish and succeed in the twenty-first century. In this inspiring, empowering book, Robinson argues for an end to the outmoded, industrial systems of mass schooling and proposes a highly personalized, organic approach that draws on today's unprecedented technological and professional resources to engage all students and develop their individual abilities and love of learning